The lived experience of accessing health services as an elderly rural individual - Skeen, Dan S (My University, 2011)
Rural communities are identified as health disparity areas due to a significant discrepancy in the overall rate of disease incidence, prevalence, morbidity, mortality, and survival rates in the rural population, as compared to the health status of the general population (National Public Health Week, 2004). This disparity is attributed to decreased access to health services experienced by rural residents, exemplified by decreased availability of health professionals (Wielandt & Taylor, 2010), limited proximity to primary care and specialty services (Baldwin et al., 2008; Wong & Regan, 2009), and challenges in receiving cancer screening and mental health services (Bettencourt, Schlegel, Talley, & Molix, 2007). Health disparities have an even greater impact on the elderly population due to a reduced physiologic reserve and increased susceptibility to illness and disability (Hinck, 2004). Much research has been done to identify these disparities with methods to rectify them, but little research has been conducted with the aim of understanding how the rural elderly view their experiences accessing health services. The purpose of this descriptive phenomenological study was to gain understanding of the experiences of rural elderly individuals in accessing health services. Information gained clarified their needs regarding access to health services with the ultimate goal of helping to rectify health disparities for the rural elderly. The study was conducted via in-depth, personal interviews. Nine participants over the age of 65 living in rural Wisconsin, and accessing rural health services for at least 10 years, were recruited through purposive sampling. With the researcher as the instrument, participants were asked open-ended questions in an attempt to capture their lived experience of accessing rural health services. Probe questions were used to further explore individual experiences when necessary. Colaizzi's method was used to analyze the data, categorizing common statements and developing themes to connect the data. Sampling ended once data saturation was reached. Three themes emerged during data analysis: (a) 50 first dates, (b) on the road again, and (c) making the most of what you have. The theme 50 first dates signified struggles faced by rural elders in maintaining continuity with their healthcare providers due to the short tenure and rapid turnover of healthcare providers in rural settings. On the road again exemplified the limited proximity of specialty services and the long commutes necessary to achieve access to such services. Making the most of what you have demonstrated the overwhelming sense of appreciation expressed by rural elders for the health services available to them, demonstrating resilience and a general feeling that access to health services is by no means limited by where they reside.
A Clinical paper submitted in partial fulfillment of the requirements for the degree of Master of Science in Nursing - Family Nurse Practitioner.
Keywords: Health services accessibility; Old age assistance; Services for older people; Aging